1989
DOI: 10.1127/ejm/01/1/0089
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonite, blueschist and eclogite formation in the southern Sesia zone (western Alps, Italy)

Abstract: The sou thern Sesia zone in the western Italian Alps consists of fou r tectonic su b-units separated by maj or thru sts. These su b-units inclu de : "gneiss minu ti" (GM) , blu eschist-facies "polymetamorphie paraschists" (PP) similar to the "11 zona diorito-k inzigitica" , "eclogitic micaschists" (E M) and blu eschist-facies "Rocca Canavese thru st sheets" (RCT). Du ring Alpine metamorphism these su b-units underw ent a polyphase early Alpine history at high-P, follow ed by a late-Alpine low-P event. Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 0 publications
3
69
0
1
Order By: Relevance
“…These estimated temperatures close to those of a previous study by Pognante (1989), who reported T = 520 45 C at P = 14 kbar, where the temperature was determined using Powell (1985) garnet clinopyroxene geothermometer.…”
Section: P-t Estimationsupporting
confidence: 70%
See 2 more Smart Citations
“…These estimated temperatures close to those of a previous study by Pognante (1989), who reported T = 520 45 C at P = 14 kbar, where the temperature was determined using Powell (1985) garnet clinopyroxene geothermometer.…”
Section: P-t Estimationsupporting
confidence: 70%
“…During the later stage of the exhumation, the EMC was overprinted by a greenschist facies metamorphism (T 400 C and P 4 5 kbar). On the other hand, Pognante (1989) reported that the southern part of the EMC underwent early Alpine eclogite facies metamorphism with peak P T conditions of T = 500 550 C and P = 13 20 kbar, and then underwent a blueschist facies metamorphism during an early stage of the exhumation, which was characterized by a significant temperature drop at high pressures (T < 450 500 C, at pressures in the jadeite lawsonite stability field). During a later stage of the exhumation, pumpellyite and albite grew under P T conditions around of T < 350 C and P < 5 kbar.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhumation was accomplished during subduction of the Alpine Tethys lithosphere Polino, Dal Piaz, & Gosso, 1990;Roda, Spalla, & Marotta, 2012;Spalla et al, 1996). Some authors (Babist et al, 2006;Giuntoli & Engi, 2016;Pognante, 1989;Ramsbotham, Inger, Cliff, Rex, & Barnicoat, 1994;Regis et al, 2014;Venturini, 1995) found evidence of a strong blueschist-to greenschistfacies retrogression within EMC, thus testifying to a heterogeneous record of the tectono-metamorphic stages. On this ground, Regis et al (2014) interpreted the SLZ as represented by a composite unit that can be divided into several slices with different pre-Mesozoic lithologies and Alpine tectono-metamorphic evolutions: (1) the Druer slice represents the southeastern portion of the SLZ and mainly consists of micaschist and minor metabasite and metagranitoid with a pervasive Alpine eclogite-facies metamorphic imprint; (2) the Intermediate Unit and GMC, in the northwestern portion of SLZ, mainly consist of fine-grained gneiss with dominant retrograde blueschist-to greenschist-facies assemblages; (3) the Fondo slice is a thin and discontinuous layer of Mesozoic metasediment with subordinate metabasite interposed between the Druer slice and GMC-Intermediate Unit.…”
Section: Geologic Outlinementioning
confidence: 99%
“…The SLZ is classically divided into four main complexes ( Figure 1(B); Compagnoni et al, 1977;Gosso, 1977): (1) the II Dioritic-Kinzigitic Zone (IIDK) preserves a pervasive pre-Alpine HT metamorphic imprint; (2) the Gneiss Minuti Complex (GMC) and (3) the EMC display a dominant Alpine metamorphic imprint and locally preserve pre-Alpine HT relicts (Compagnoni et al, 1977;Gosso, Messiga, Rebay, & Spalla, 2010;Lardeaux, Gosso, Kiénast, & Lombardo, 1982;Manzotti et al, 2014;Zanoni, 2016); (4) the Rocca Canavese Thrust Sheets are characterized by a blueschist Alpine imprint with no eclogite-facies relicts (Cantù, Spaggiari, Zucali, Zanoni, & Spalla, 2016;Pognante, 1989;Spalla & Zulbati, 2003). The EMC and GMC consist of metapelite, paragneiss, metagranitoid, metabasite, and impure marble recording Alpine polyphasic deformation and eclogite-facies peak conditions.…”
Section: Geologic Outlinementioning
confidence: 99%